2012
DOI: 10.1093/nar/gks035
|View full text |Cite
|
Sign up to set email alerts
|

ATM regulates proteasome-dependent subnuclear localization of TRF1, which is important for telomere maintenance

Abstract: Ataxia telangiectasia mutated (ATM), a PI-3 kinase essential for maintaining genomic stability, has been shown to regulate TRF1, a negative mediator of telomerase-dependent telomere extension. However, little is known about ATM-mediated TRF1 phosphorylation site(s) in vivo. Here, we report that ATM phosphorylates S367 of TRF1 and that this phosphorylation renders TRF1 free of chromatin. We show that phosphorylated (pS367)TRF1 forms distinct non-telomeric subnuclear foci and that these foci occur predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 47 publications
6
42
1
Order By: Relevance
“…Immunofluorescence was performed as described (Mitchell and Zhu, 2014;Zhu et al, 2003). FISH analysis was carried out essentially as described (McKerlie et al, 2012). For triple staining, blocked coverslips were incubated with both rabbit anti-pT371 (at 1:500) and mouse anti-PML (at 1:200) antibodies in blocking buffer (1 mg/ml BSA, 3% goat serum, 0.1% Triton X-100 and 1 mM EDTA in PBS) at room temperature for 2 h. After three washes in PBS, coverslips were incubated with both TRITC-conjugated donkey anti-rabbit (1:250; Cat.…”
Section: If-fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence was performed as described (Mitchell and Zhu, 2014;Zhu et al, 2003). FISH analysis was carried out essentially as described (McKerlie et al, 2012). For triple staining, blocked coverslips were incubated with both rabbit anti-pT371 (at 1:500) and mouse anti-PML (at 1:200) antibodies in blocking buffer (1 mg/ml BSA, 3% goat serum, 0.1% Triton X-100 and 1 mM EDTA in PBS) at room temperature for 2 h. After three washes in PBS, coverslips were incubated with both TRITC-conjugated donkey anti-rabbit (1:250; Cat.…”
Section: If-fishmentioning
confidence: 99%
“…715-156-150, Jackson Laboratories) at room temperature for 30 min. Subsequently, coverslips were processed as described (McKerlie et al, 2012). Cell images were then recorded on a Zeiss Axioplan 2 microscope with a Hammamatsu C4742-95 camera and processed in Open Lab.…”
Section: If-fishmentioning
confidence: 99%
“…In addition, TRF1 deficiency results in lower cellular multiplication, increasing G2 arrest and mitotic inactivity [45]. It is further demonstrated that TRF1 abraogation inhibits the growth of aggressive lung carcinomas independently of telomere length and p53 status [45].…”
Section: In Vivo Effect Of Trf1-deletion On Tumorigenesismentioning
confidence: 96%
“…It is characteristic that TRF1 deletion results in the accumulation of γ-H2AX at telomeric DNA, leading to the instability of chromosomes [43,44]. In addition, TRF1 deficiency results in lower cellular multiplication, increasing G2 arrest and mitotic inactivity [45]. It is further demonstrated that TRF1 abraogation inhibits the growth of aggressive lung carcinomas independently of telomere length and p53 status [45].…”
Section: In Vivo Effect Of Trf1-deletion On Tumorigenesismentioning
confidence: 97%
“…93,[98][99][100][101] While phosphorylation of TRF1 by Plk1 and CK2 increases TRF1-telomere interaction, ATMmediated phosphorylation appears to inhibit association of TRF1 with telomeres, thereby promoting telomere elongation, such that ATM inhibition leads to telomere shortening. The latter is consistent with the elevated rate of telomere shortening observed in cells from patients with ataxia telangiectasia (AT), a disease caused by ATM mutation.…”
Section: Additional Posttranslational Modifications Of Telomeric Chromentioning
confidence: 99%